Augustine Shutte’s autobiographical account of his Christian theology - Giddy, Patrick (Stellenbosch Theological Journal, 2016)
Before his death in May this year (2016) Augustine Shutte wrote an “autobiographical account” of a selection of his theology papers that situates his writings within his public involvement in church and society – seminary, academy, the Catholic Church, African culture, a thought-world of science and secularity. The account also documents a pattern of development in his understanding of Christian faith that arises out of this involvement. As such the narrative constitutes a theological reflection on God’s self-communication in Jesus in the context of doctrinal formulations and traditional church practices that cry out for rethinking. The influence of Karl Rahner is evident throughout but his narrative also acknowledges his two formative teachers, at Stellenbosch and UCT, as his theology as a whole can be seen as an exercise in secularisation (Johan Degenaar) through a truly personal and existential appropriation of our Christian heritage (Martin Versfeld). The narrative is introduced by myself through a brief account of its author and of the genesis of the article.